2008
DOI: 10.1080/00986280802201976
|View full text |Cite
|
Sign up to set email alerts
|

Review ofToPTeaching Strategies: Links to Students' Scientific Inquiry Skills Development

Abstract: A major function of instruction in psychology is to convey complex phenomena in a manner accessible to students. Instructors using well-designed teaching activities can help to make complex material accessible. We content analyzed teaching activities reported in the first 33 years of Teaching of Psychology. We identified 15 general teaching strategies in 681 teaching activity articles and coded strategies' potential impact on student development of scientific inquiry skills. We found that ToP authors have cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Research has identified various teaching strategies that optimize student learning and facilitate the understanding and retention of information (Tomcho et al, 2008). In western contexts, teaching approaches that encourage active engagement with the material, as well as critical thinking and evaluation are known to exert a positive impact on learning outcomes (Butler, Phillmann, & Smart, 2001;Freeman et al, 2007;O'Sullivan & Copper, 2003;Prince & Felder, 2006;Sivan, Wong Leung, Woon, & Kember, 2000;Yoder & Hochevar, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified various teaching strategies that optimize student learning and facilitate the understanding and retention of information (Tomcho et al, 2008). In western contexts, teaching approaches that encourage active engagement with the material, as well as critical thinking and evaluation are known to exert a positive impact on learning outcomes (Butler, Phillmann, & Smart, 2001;Freeman et al, 2007;O'Sullivan & Copper, 2003;Prince & Felder, 2006;Sivan, Wong Leung, Woon, & Kember, 2000;Yoder & Hochevar, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified various teaching strategies that optimize student learning and facilitate the understanding and retention of complex information (Tomcho et al, 2008). Learning approaches that encourage active engagement with the material, as well as critical thinking and evaluation, are known to exert a positive impact on learning outcomes (Butler, Phillmann, & Smart, 2001;Freeman et al, 2007;O'Sullivan & Copper, 2003;Prince & Felder, 2006;Sivan, Wong Leung, Woon, & Kember, 2000;Yoder & Hochevar, 2005).…”
Section: Abstract: Active Learning Exercise Journal Excerpts Statismentioning
confidence: 98%
“…In addition, inquiry-based learning integrates many strategies throughout its steps, its components, and associated teaching practices, including problem-solving, brainstorming and discussions in collaborative groups (Dunlap & Antonio, 2012). Furthermore, there are set of skills related to developing creative of the students' through using inquiry-based learning and brainstorming as follows (Tomcho et al, 2008, Ormond, 2011):…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Contemporary trends in teaching and learning have moved from direct learning strategies to active learning strategies, and include many strategies, including inquiry-based learning and brainstorming. These strategies start from a set of principles, the most important of which are the following (Tomcho et al, 2008):…”
Section: Introduce the Problemmentioning
confidence: 99%